Forensic Hydrochemistry for Environmental Crime Investigation: A PRISMA-Based Systematic Review of Isotopic and Geochemical Fingerprinting Techniques - Wali, Saadu U.; Alias, Noraliani B.; Kaoje, Ismail U.; Ibrahim, Sa’ad; Usman, Abdullahi B. (Global Journal of Earth Science and Engineering, 2025)
Forensic hydrochemistry applies chemical and isotopic analysis to water systems, providing powerful tools for investigating environmental crimes such as illegal dumping, groundwater pollution, and oil spills. This review systematically examined seventy-five (75) articles following PRISMA guidelines, highlighting techniques such as stable isotope analysis, compound-specific isotope analysis (CSIA), geochemical fingerprinting, and advanced mass spectrometry. Results show isotopic tracers effectively differentiate natural from anthropogenic sources, though CSIA offers direct evidence of contaminant degradation, strengthening legal accountability. Geochemical and hydrocarbon fingerprinting further support source attribution, though challenges persist due to overlapping isotopic ranges, high analytical costs, and baseline data gaps. Emerging approaches, such as LC-HRMS for persistent pollutants, expand forensic applications. Overall, forensic hydrochemistry advances environmental justice by enabling reliable pollution attribution, improving litigation outcomes, and contributing to sustainable water resources management.
Keywords: Stable isotope tracing, Environmental forensics, Geochemical fingerprinting, Water pollution source apportionment, Compound-specific isotope analysis (CSIA).